RECONSTRUCTION OF PEDAGOGICAL ACTIVITIES IN HIGHER EDUCATION - Ksenia L. Polupan (Высшее образование в России)
The article focuses on the main causes of the "weaknesses" in the system of higher education. The analysis of the requirements to pedagogical activities shows that these causes relate to various factors including new regulatory framework for educational programs, late submission of information about current changes, changes in the type of students' activities, etc. Some of the ways to change the pedagogical activities in higher education were identified and classified. These ways called 3C system (communication, cooperation, construction) will lead to more efficient educational process based on interactive ways of working with students in order to form their practical experience.